ISYTIQÂQ: Media Pengembangan dan Adaptasi Bahasa Arab - Suaidi Suaidi (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2014)
Isytiqâq plays a great role in developing Arabic words in order to fit new words which are not available in various aspects of life such as new concepts, technology, etc. By isytiqâq, new words can be formed, and developed by employing abundance of Arabic word forms. Isytiqâq also enables Arabic to reveal grammatical functions. Isytiqâq, however, has been one of several topics which were subject to controversy. Grammarians from Kûfah and Bashrah had their own opinions about the origins of isytiqâq. In addition, differences are there between classical and modern linguists surrounding the kinds of isytiqâq which are all to deal with in this peace of paper.